Ion-dependent electroluminescence from trivalent rare-earth doped n-ZnO/p-Si heterostructured light-emitting diodes - Iwan, S. (2016)
We have demonstrated rare earths (REs) doped ZnO-based heterojunction light-emitting diodes (LEDs) on p-Si substrates by ultrasonic spray pyrolisis (USP). Room-temperature electroluminescence was clearly observed from reverse-biased n-ZnO:REs/p-Si diodes, which red and blue color emissions were realized from Eu and Tm ions, respectively. The narrow line-width emissions are attributed to the transitions within the shielded 4f levels of the trivalent REs ions that resulting from direct electron impact excitation during reverse bias.